Folk linguistics and sociolinguistics: concepts of the language situation in Russian and Belarusian Internet communication - Bobko, Tatyana V. (Journal of the Belarusian State University. Philology, 2023)
The article discusses the attitude of Russian- and Belarusian-speaking Belarusians to the language of the country that is currently not used by them in Internet communication (Belarusian and Russian languages, respectively). The purpose of the article is to determine those sociolinguistic characteristics of the Russian and Belarusian languages that become the object of attention and comprehension in the naive linguistic ideas of Russian and Belarusian speakers. It was found that the attitude to the two languages of the Belarusian society can be expressed both in explicit metalinguistic statements about these languages, and in an implicit form (by switching codes). Both explicit and implicit metalinguistic statements have both signifcant similarities and a number of important diﬀerences in terms of quantity, subject matter, and functions. The patterns obtained suggest that the ideas about the coexistence and competition of the Russian and Belarusian languages within the language situation in Belarus aﬀect speech practices, determining the range of situations in which speakers pay attention to the language that is not their preferred language of communication, and determining meaningful and pragmatic characteristics of metalinguistic comments.